MEDIA PEMBELAJARAN BERBASIS VIDEO DALAM MENINGKATKAN MOTIVASI BELAJAR PROTOZOA DAN MIKROALGA MAHASISWA PENDIDIKAN BIOLOGI PADA MATA KULIAH PROTISTA - Siti Nuraisyah; Miftah Farid; rapsan rapsan; Anis Tri Fransiska; Prita Asminitya Sari; Nadia Pratiwi; Ayu Ramayanti; Didimus Tanah Boleng; Eadvin Rosrinda; Dora Dayu Rahma Turista (BIO-EDU: Jurnal Pendidikan Biologi, 2023)
Video media is a medium that provides information in the form of sound and visuals. Based on the results of observations obtained from biology education students who have received protist courses, the learning process is still centered on educators and textbooks or manuals, so students tend to be passive or lack interest and motivation to learn. Phenomena that are happening a lot at this time, for example when practicum activities take place only use manuals to find out how the activities will work, thus making some students not understand clearly the steps of the work being carried out. The purpose of this research is to increase student learning motivation in the Protist course. The application of videos can provide opportunities for students to collect information and make it easier to carry out learning activities. The subjects of this study were biology education students from class of 2019 and below with the condition that they had passed the protista course with a total of 55 respondents. The research instrument was conducted using qualitative and quantitative methods. The validity test results obtained had a significant value <0.05, namely 0.000 <0.05 and the reliability test had a Cronbach's Alpha value of 0.821 > 0.70. The conclusion obtained by video media is effective in helping the learning process.